Hubungan Lama Menderita dan Manajemen Diri dengan Kontrol Glikemik pada pasien Diabetes Mellitus - Ade Novianti; Dewi Prabawati; Indriati Kusumaningsih (Jurnal Keperawatan Florence Nightingale, 2026)
Diabetes mellitus (DM) is as a chronic metabolic illness with a high prevalence that may leads to various complications. HbA1C level is used primary indicator to evaluate whether diabetes management is well controlled. This study aimed to analyze the relationship between duration of illness and self-management with Glycemic control among patients with diabetes mellitus at Hospital X Jakarta. This study employed a quantitative study with descriptive correlation and cross-sectional approach. A total of 62 respondents were selected using purposive sampling technique based on inclusive and exclusive criteria. Data were collected using instrument of DSMI (Diabetes Self-Management Instrument) questionnaire and HbA1C from medical record. Data were analyzed with Kendall’s tau C statistical test. The result showed significant relationship between self-management with HbA1C level with p-value of 0.022 (p<0.05). Meanwhile, there was no significant association between duration of illness with HbA1C level with p-value of 0.143 (p>0.05). The findings indicated that patients with lower self-management tended to have uncontrolled HbA1C levels, whereas patients with a longer duration of DM tended to demonstrate poorer glycemic control, although the association was not statistically significant.  This study suggests that nurses should provide education and health intervention to improve patient’s self-management in order to prevent complications and enhance quality of life.